High Copy-Number Variation Burdens in Cranial Meningiomas From Patients With Diverse Clinical Phenotypes Characterized by Hot Genomic Structure Changes - Ma, Junpeng; Hong, Yaqiang; Chen, Wei; Li, Da; Tian, Kaibing; Wang, Ke; Yang, Yang; Zhang, Yuan; Chen, Yujia; Song, Lairong; Chen, Liangpeng; Zhang, Liwei; et al. (Frontiers in Oncology, 2020)
Meningiomas, as the most common primary tumor of the central nervous system, are known to harbor genomic aberrations that associate with clinical phenotypes. Here we performed genome-wide genotyping for cranial meningiomas in 383 Chinese patients and identified 9,821 copy number variations (CNVs). Particularly, patients with diverse clinical features had distinct tumor CNV profiles. CNV burdens were greater in high-grade (WHO grade II and III) samples, recurrent lesions, large tumors (diameter > 4.3 cm), and those collected from male patients. Nevertheless, the level of CNV burden did not relate to tumor locations, peritumoral brain edema, bone invasion, or multiple lesions. Overall, the most common tumor CNVs were the copy number gain (CNG) at 22q11.1 and the copy number losses (CNLs) at 22q13.2, 14q11.2, 1p34.3 and 1p31.3. Recurrent lesions were featured by the CNLs at 1p31.3, 6q22.31, 9p21.3 and 11p12; and high-grade samples had more CNVs at 4q13.3 and 6q22.31. Meanwhile, large tumors were more likely to have the CNVs at 1p31.3 and 1p34.3. Additionally, recurrence prediction indicated the CNLs at 4p16.3 (p-value= 0.009, Hazard Ratio = 5.69) and 10p11.22 (p-value= 0.037, Hazard Ratio = 4.53) were candidate independent risk factors.